Epos: the winged flame - Blade, Adam; Tucker, Ezra N. (Scholastic New York, 2008)
Tom must face the Winged Flame, a phoenix living inside a volcano, to finish his quest to save the kingdom from the dark wizard Malvel, but during the fight he learns about his mysterious past and what it means for his future